2020
DOI: 10.3390/cancers12113387
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence after Robot-Assisted Radical Hysterectomy for Early-Stage Cervical Cancer: A Multicenter Retrospective Study

Abstract: This retrospective analysis aimed to assess the risk factors for recurrence in patients diagnosed with early-stage cervical cancer (≤IB1 or IIA1, FIGO 2009) undergoing robot-assisted radical hysterectomy in Spain and Portugal between 2009 and 2018. A second primary objective was to audit the oncological outcomes according to quality indicators (QI) proposed by the European Society of Gynecology Oncology (ESGO). The study population included 239 women. After a median follow-up of 51 months, recurrence occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
1
2
Order By: Relevance
“…The lower rates of complications observed in group A (Table S1, Supplementary Material) support this hypothesis. In contrast to the findings of other studies [3], our data indicated that the use of an intrauterine manipulator is not associated with worse clinical outcomes [25]. The application of protective maneuvers may partly explain some of the recurrences in patients who undergo MIS.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The lower rates of complications observed in group A (Table S1, Supplementary Material) support this hypothesis. In contrast to the findings of other studies [3], our data indicated that the use of an intrauterine manipulator is not associated with worse clinical outcomes [25]. The application of protective maneuvers may partly explain some of the recurrences in patients who undergo MIS.…”
Section: Discussioncontrasting
confidence: 97%
“…In our study population, ultrastaging allowed the detection of three micrometastases (mi) and three isolated tumor cells (itc) in group A and 0 mi/itc in group B. While a recent well-designed retrospective study observed a significantly decreased DFS in patients affected by micrometastases [31], an ancillary study in- In contrast to the findings of other studies [3], our data indicated that the use of an intrauterine manipulator is not associated with worse clinical outcomes [25]. The application of protective maneuvers may partly explain some of the recurrences in patients who undergo MIS.…”
Section: Discussioncontrasting
confidence: 60%
“…As yet four studies have been published analyzing the ESGO QIs [6,[9][10][11]. The objective of three studies was to audit the quality of surgery for early cervical cancer according to the QIs proposed by ESGO.…”
Section: Results In the Context Of The Published Literaturementioning
confidence: 99%
“…Robot-assisted laparoscopic approach for major surgery offers several advantages including minimally surgical trauma, less blood loss, and faster recovery (1)(2)(3). However, the Trendelenburg position and CO 2 pneumoperitoneum required for such surgery are highly associated with significant changes in cerebral hemodynamic physiology and intracranial pressure (ICP) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%